HUBUNGAN FASE KEMOTERAPI DENGAN STATUS GIZI ANAK LEUKEMIA - Siska Rani Ramadhani; Yufitriana Amir; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The main treatment of leukemia to get remission is chemotherapy. Chemotherapy generally cause various side effects that cause the child’s food intake is not fulfilled. It makes child at risk of malnutrition. The aim of this research is to examine the relationship between chemotherapy phase to the leukemia child’s nutritional status. This research uses observational analytic research design with cross sectional approach. Samples of this research are 30 children with leukemia based on inclusion and exclusion criteria using purposive sampling techniques. This research uses Patient Generated Subjective Global Assessment Short From (PG-SGA SF) questionnaire to measuring nutritional status and describing nutrition impact symptoms. The research uses univariate and bivariate analysis using Kolmogorov-Smirnov. The result shows that form 30 leukemia children who get chemotherapy, 19 respondents (63,3%) are boy, 28 respondents (93,3%) suffering from Acute Leukemia Lymphoblastic (ALL), and 19 respondents (63,3%) are on the maintenance phase of chemotherapy. The mean age of children with leukemia is 6,27 years old and the mean age of children when first diagnosed with leukemia is 4,9 years old. Nutrition impact symptoms show that 16 respondents (53,3%) feel nausea and 15 respondents (50,0%) feel dry mouth. 22 respondents (73,3%) are well-nourish. The result of bivariate analysis shows p value = 0,460 > α (0,05) which is means that chemotherapy have no relationship with the leukemia child’s nutritional status. Based on the results of the research, it is expected that nurses and families can fulfill the nutritional needs of children who undergo chemotherapy to improve nutritional status. Keywords: chemotherapy, leukemia, nutritional status, PG-SGA SF